CONSIDERATIONS ON THE MANAGEMENT OF INTANGIBLE CULTURAL HERITAGE OF GEORGIA - Imnaishvili, Nino; Taktakishvili, Marina (European Scientific Journal, ESJ, 2014)
During the past decades the concept of Intangible Cultural Heritage has been established in Georgia. The state takes care of safeguarding of the intangible cultural heritage of Georgia and other peoples on the territory of Georgia, as well as the intangible cultural heritage bearing the Georgian sign beyond Georgia. Georgia acceded to the UNESCO Convention in the early 2008. In 2007-2012 Georgia submitted the nomination â€œAncient Georgian traditional Qvevri wine-making methodâ€; the mechanism of registration of elements of intangible cultural heritage was developed and approved; pilot inventories were carried out, etc. For the purpose of identification, inventory, protection, preservation and in some cases restoration of intangible cultural heritage of Georgia it is highly important to establish a decentralized management system and to bring it into compliance with administrative, legislative, managerial, financial, informational, human resources, material-technical resources. In addition to that, it is critical to ensure involvement of state, private and nongovernmental structures and local communities; diversification of funding sources; information support at the local, national and international level. Moreover, it is necessary to enusre the protective system of the sector with respective human resources, involvement of the museum network, cultural-educational institutions in the process of searching, recording and restoration of elements of intangible cultural heritage.